MARRIED AL-GHAZALI PERSPECTIVE STUDY CONCEPT AND STRATEGY - Abdullah Abdullah (Universitas Islam Negeri (UIN) Mataram, 2019)
Studying Al-Ghazali's thoughts about the concept of marriage is very interesting, at least due to two things, First Al-Ghazali individually is an Islamic scientist in almost all disciplines, his title as Hujjatul Islam is a form of indisputable recognition, Secondly, Concept Al-Ghazali concocting the concept of marriage does not stop at the legal dimension, but is framed with ethics on how to realize a substantial vision of marriage, so that the concept of marriage that is built has a spirit of change towards happiness. The concept of marriage offered by Al-Ghazali is expected to be able to realize social transformation in the community. According to Al-Ghazali Creating a harmonious and lasting family must go through three stages, the first is the pre-marital stage which includes the development of motivation and selection criteria. The criteria are divided into two halal criteria and ideal criteria (eligibility). Second, Post-Marriage, In Post-Marriage Proportional interactions are the key to harmony among the interactions that must be considered by the couple is, Holding Walimah. Be Understanding of Spouse, Husband must give time to rest, recreation and fun to his wife, Husband must maintain authority by being assertive, Proportional in Jealousy, Proportional in Living, Teaching Religious Law to the Family, Caring for Jima'. Third, the resolution of problems in the household must be wise. In general, the concept of marriage of Al-Ghazali is built on the principle of Proportionality, so the key to building harmony and household integrity is on Proportionality in interactions with spouses.